The Ethanolic Extract of Caesalpinia sappan Heartwood Inhibits Cerebral Ischemia/Reperfusion Injury in a Rat Model Through a Multi-Targeted Pharmacological Mechanism - Wan, Yan-Jun; Xu, Li; Song, Wen-Ting; Liu, Yu-Qi; Wang, Li-Chao; Zhao, Ming-Bo; Jiang, Yong; Liu, Lian-Ying; Zeng, Ke-Wu; Tu, Peng-Fei (Frontiers in Pharmacology, 2019)
Background: Caesalpinia sappan L. (C. sappan) is a traditional Chinese medicinal plant. The dried heartwood of C. sappan (also known as Sappan wood) has been widely used for the folkloric medical treatment of ischemic cerebral stroke in China. However, the detailed underlying pharmacological mechanism still remains largely unexplored. Methods: In this study, a middle cerebral artery occlusion (MCAO) rat model was employed to elucidate the mechanism of the anti-cerebral ischemic effects of C. sappan ethanolic extract (CEE). Moreover, systemic multi-target identification coupled with gene ontology biological process (GO BP) and reactome pathway analysis was used to investigate the potential neuroprotective mechanism. Furthermore, the presumed mechanism was confirmed through biological analysis by determining the effects of CEE on the identified signaling pathways in PC12 cells model-induced by oxygen-glucose deprivation/reperfusion (OGD/R). Results: Our study demonstrates that CEE (both through in vivo administration at a dosage of 300 mg/kg and through in vitro incubation at a dosage of 2.4 μg/mL) is a neuroprotective agent that can effectively inhibit neuronal damage, promote synaptic generation, and suppress the activation of neutrophils, microglia and astrocytes. Moreover, the neuroprotective mechanism of CEE is mediated via regulating 150 potential target proteins, which are associated with 6 biological processes and 10 pathways, including JAK-STAT, HSP90 and DNA damage/telomere stress. Conclusion: CEE can exert neuroprotective effect through multi-target pharmacological mechanisms to prevent ischemia/reperfusion-induced cerebral injury.